Egocentric cues influence the allocentric spatial memory of object configurations for memory-guided actions - ster, Pierre-Pascal; Fiehler, Katja; Karimpur, Harun (Journal of neurophysiology, 2023)
Allocentric and egocentric reference frames are used to code the spatial position of action targets in reference to objects in the environment, i.e., relative to landmarks (allocentric), or the observer (egocentric). Previous research investigated reference frames in isolation, for example, by shifting landmarks relative to the target and asking participants to reach to the remembered target location. Systematic reaching errors were found in the direction of the landmark shift and used as a proxy for allocentric spatial coding. Here, we examined the interaction of both allocentric and egocentric reference frames by shifting the landmarks as well as the observer. We asked participants to encode a three-dimensional configuration of balls and to reproduce this configuration from memory after a short delay followed by a landmark or an observer shift. We also manipulated the number of landmarks to test its effect on the use of allocentric and egocentric reference frames. We found that participants were less accurate when reproducing the configuration of balls after an observer shift, which was reflected in larger configurational errors. In addition, an increase in the number of landmarks led to a stronger reliance on allocentric cues and a weaker contribution of egocentric cues. In sum, our results highlight the important role of egocentric cues for allocentric spatial coding in the context of memory-guided actions.NEW & NOTEWORTHY Objects in our environment are coded relative to each other (allocentrically) and are thought to serve as independent and reliable cues (landmarks) in the context of unreliable egocentric signals. Contrary to this assumption, we demonstrate that egocentric cues alter the allocentric spatial memory, which could reflect recently discovered interactions between allocentric and egocentric neural processing pathways. Furthermore, additional landmarks lead to a higher contribution of allocentric and a lower contribution of egocentric cues.Allocentric and egocentric reference frames are used to code the spatial position of action targets in reference to objects in the environment, i.e., relative to landmarks (allocentric), or the observer (egocentric). Previous research investigated reference frames in isolation, for example, by shifting landmarks relative to the target and asking participants to reach to the remembered target location. Systematic reaching errors were found in the direction of the landmark shift and used as a proxy for allocentric spatial coding. Here, we examined the interaction of both allocentric and egocentric reference frames by shifting the landmarks as well as the observer. We asked participants to encode a three-dimensional configuration of balls and to reproduce this configuration from memory after a short delay followed by a landmark or an observer shift. We also manipulated the number of landmarks to test its effect on the use of allocentric and egocentric reference frames. We found that participants were less accurate when reproducing the configuration of balls after an observer shift, which was reflected in larger configurational errors. In addition, an increase in the number of landmarks led to a stronger reliance on allocentric cues and a weaker contribution of egocentric cues. In sum, our results highlight the important role of egocentric cues for allocentric spatial coding in the context of memory-guided actions.NEW & NOTEWORTHY Objects in our environment are coded relative to each other (allocentrically) and are thought to serve as independent and reliable cues (landmarks) in the context of unreliable egocentric signals. Contrary to this assumption, we demonstrate that egocentric cues alter the allocentric spatial memory, which could reflect recently discovered interactions between allocentric and egocentric neural processing pathways. Furthermore, additional landmarks lead to a higher contribution of allocentric and a lower contribution of egocentric cues.